(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: There is a widespread belief for the efficacy of preemptive analgesia among clinicians. Different drugs and methods are used as preemptive analgesic method for postoperative pain management. Objective: To evaluate the efficacy of preemptive use of small dose intravenous ketamine on post operative pain on patients undergoing laparoscopic cholecystectomy. Materials and Methods: Sixty patients of both sexes as per American Society of Anaesthesiologists (ASA) physical status I and II underwent laparoscopic cholecystectomy were randomly allocated into two groups. In the operating room, Group A (n=30) received 0.5 mg/kg body weight of ketamine intravenously 10 minutes before the surgical incision. In Group B (n=30) 0.5 mg/kg body weight of normal saline was injected. Post operative analgesia was maintained with on demand intramuscular pethidine 1.5 mg/kg body weight. The pain intensity was assessed at time 0 (immediately after arousal) and 6, 12, and 24 hours postoperatively using the 10 points visual analogue scale (VAS). Side effects like nausea, vomiting, delirium and hallucination were also recorded. Results: For all of the evaluated times, the VAS score were significantly lower in Group A with ketamine compared to Group B with normal saline. The interval time for the first analgesic request was 22.9±6.8 (Mean±SD) minutes in Group A and 17.8±7.2 (Mean±SD) minutes in Group B and the difference was statistically significant (P=0.021). The total number of pethidine injections in first 24 hours postoperatively was 0.7±0.6 (Mean±SD) in Group A and 1.9±0.7 (Mean±SD) in Group B and the difference was statistically significant (P=0.037). The mean total cumulative amount of pethidine administered over 24 hrs period following the end of surgery in group A was 97.31±10.12 mg (Mean±SD) and in group B was 151.23±12.02 mg (Mean±SD) and the difference was statistically significant (P=0.008). Conclusion: A low dose of intravenously administered ketamine had a preemptive effect in reducing pain after laparoscopic cholecystectomy. Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 35-39